QTL Mapping and Validation for Kernel Area and Circumference in Common Wheat via High-Density SNP-Based Genotyping - Ren, Tianheng; Fan, Tao; Chen, Shulin; Ou, Xia; Chen, Yongyan; Jiang, Qing; Diao, Yixin; Sun, Zixin; Peng, Wanhua; Ren, Zhenglong; Tan, Feiquan; Li, Zhi (Frontiers in Plant Science, 2021)
As an important component, 1,000 kernel weight (TKW) plays a significant role in formation of yield traits of wheat. Kernel size is significant positive correlation to TKW. Despite the fact that numerous loci for kernel size in wheat have been reported, our knowledge on loci for kernel area (KA) and kernel circumference (KC) remains to be limited. In the present study, a RIL population containing 371 lines genotyped using the Wheat55K SNP array was used to map QTLs controlling the KA and KC in multiple environments. A total of 54 and 44 QTLs were mapped by using the BIP or MET module of the ICIM method, respectively. Twenty-two QTLs of them were considered major QTLs. BLAST analysis showed that major and stable QTLs QKc.sau-6A.1 (23.12-31.64 cM on 6A) for KC and QKa.sau-6A.2 (66.00-66.57cM on 6A) for KA were likely novel QTLs, which explained 22.25% and 20.34% of the phenotypic variation on average in the three-year experiments, respectively. Two Kompetitive Allele-Specific PCR (KASP) markers, KASP-AX-109894590 and KASP-AX-109380327, were developed and tightly linked to QKc.sau-6A.1 and QKa.sau-6A.2, respectively, and the genetic effects of the different genotypes in the RIL population were successfully confirmed. Furthermore, in the interval where QKa.sau-6A.2 was located on Chinese Spring and T. Turgidum ssp. dicoccoides reference genomes, only eleven genes were found. In addition, digenic epistatic QTLs were also showed important influence to KC and KA. Altogether, the results revealed the genetic basis of KA and KC and will be useful for the marker assistance selection (MAS) of lines with different kernel sizes, laying the foundation for the fine mapping and cloning of the gene(s) underlying the stable QTLs detected in this study.